COMPOSITION OF ASCOLICHEN IN GAYO HIGHLAND - W Wardiah; Desi Ratnasari; I Iswadi; S Samingan; Dewi Andayani (Universitas Islam Negeri Ar-Raniry, 2021)
Ascolichen is group of lichen composed by ascomycetes (the mycobiont) and algae (the photobiont) species which play ecological and industrial roles. The campus area of Syiah Kuala University Gayo Lues is a part of the Gayo Highland which has specific environmental characteristics. The research aim was to determine the ascolichen species, the type of talus and the substrate characteristics. This study used a qualitative approach with research type was an exploratory survey. Data collection was carried out at 2 stations, namely Station I (campus area) and Station 2 (outside campus area). Data was analyzed descriptively. The results showed that there were 28 species of ascolichen found in the location which belong 3 classis, 6 orders, 15 families, and 25 genera. Moreover, the thallus types of lichen species were crustose (16 species), foliose (8 species), and fruticose (4 species). The types of lichen substrate were tree trunks (22 species), dead woods (9 species) and rocks (4 species). The acidity of the substrates ranges 4-6 (acidic).